Elusive group 14 elemental species stabilized by amidinato silylenes - Wee, Meldon Yi Shuo (Nanyang Technological University, 2024)
This thesis describes the synthesis and isolation of a series of Group 14 elemental clusters bearing challenging and unique structural characteristics, all stabilized by an amidinato silylene ligand system. In Chapter 2, the synthesis of a remarkable heavier analogue of spiro[3.3]hepta-1,2,5,6-tetraene 2.4 is described. Its unique structure bearing two simultaneous strained cyclic allene moieties can also be described as simultaneous silylones, monatomic silicon(0) species stabilised by a tetradentate silylene ligand. Its reactivity to W(CO)5·THF results in the formation of an bis(pentacarbonyl tungsten)- spiroheptasiladione adduct 2.8 demonstrating its Lewis Basicity. The structures of other co-products, 2.6 and 2.7, from its synthesis shed light on its proposed synthetic pathway. In Chapter 3, the transfer of digermanium(0) to amidinato silylene to from a digermadisilacyclobutadiene complex 3.2 is demonstrated. Stepwise growth of a germanium cluster is also demonstrated resulting the synthesis and isolation of a bis(trigermanium(0)) complex 3.3. Preliminary results demonstrating the release of trigermanium (0) species towards the preparation of amorphous germanium nanoparticles are also described